Proyecto de creación de imagen corporativa, - Solórzano Naranjo., Martha De Jesús (2010)
The television has been from his beginnings the most important communication media in the history of the humankind, due to the great impact that had in the lives of millions people, to the being a way of diffusion totally different from those who already existed, since it was incorporating images in movement besides the traditional elements as sound and text. Nowadays people have become very selective with regard to what they see in the television, if something is not of his pleasure, simply choose not to see it. Everything evolves, for this reason, the television also they have done it, innovating in the content of his programs, looking for new alternatives that manage to satisfy the television viewer. The Tv channel Brisa TV, based in Salinas, Santa Elena, is the pioneer tv network in the zone, maintaining its position as the leader of the peninsular television for 7 years, but its Corporative Image and Television Programming has been jammed for quite some time. This is the reason for this renovation project that includes a new corporate image for Brisa Tv, along with a new name: Santa Elena TV, also new standard programming and a new pilot show, focused on fulfilling the needs of the peninsular viewer